Colne Bridge (Huddersfield) WWTW - Biopur plant process design and performance - Holmes, J.; Dutt, S. (Cranfield University, School of Water Sciences, 1999)
The complexity of the Huddersfield works and the issues addressed by the scheme design engineers are highlighted, including the need for a robust nitrification process due to the high levels of nitrification inhibition in the plant feed. Issues influencing the Biopur process selection are discussed and a detailed description of the Biopur process design is given, together with details on process commissioning and performance testing. Finally the plant performance to date is summarised together with a list of issues for consideration on future plants.